The identity of Fordia microphylla and lectotypification of Millettia pulchra (Fabaceae: Millettieae) - Song, Zhuqiu; Ouyang, Xuejun; Zuo, Lei; Huang, Zhongliang (Phytotaxa, 2017)
The non-monophyletic genus Fordia is hardly distinguished from some taxa of the polyphyletic genus Millettia of the same tribe Millettieae (Fabaceae). Examination of both literature and specimens shows that the Chinese species Fordia microphylla is conspecific with the widely distributed species Millettia pulchra. Some nomenclatural questions on Fordia microphylla are clarified, and the lectotype of Millettia pulchra is designated.